Processed food consumption is associated with diet quality, but not weight status, in a sample of low-income and ethnically diverse elementary school children. (1st August 2020) - Bleiweiss-Sande, Rachel; Sacheck, Jennifer M.; Chui, Kenneth; Goldberg, Jeanne P.; Bailey, Caitlin; Evans, E. Whitney
Abstract: Excess consumption of highly processed foods may be associated with lower diet quality and obesity prevalence, but few studies have examined these relationships in children from low-income households. Therefore, the objective of this study was to evaluate the relationship between food consumption by processing category, diet quality as measured by the Healthy Eating Index-2015 (HEI-2015) and body mass index (BMI) in a sample of low-income children. Data from a study assessing the impact of Summer Food Service participation on diet quality and weight status (N = 131) was used to conduct a cross-sectional analysis of children aged six to twelve years from low-income communities in the Northeastern U.S. Total HEI-2015 score and percentage of calories consumed by processing level were computed per day from three 24-h diet recalls. Multivariable linear regression was used to assess the relationship between percentage of calories from foods by processing category (unprocessed and minimally, basic, moderately and highly processed), HEI-2015 and BMI-z score. The final sample was 58% male and 33.8% obese. On average, children consumed 39.8 ± 17.2% of calories from highly processed foods. A 10% increase in calories consumed from highly processed foods was associated with a 2.0 point decrease in total HEI-2015 score [95% CI (−2.7, −1.2)], and a 10% increase in calories from minimally processed foods was associated with a 3.0 increase in HEI-2015 score [95% CI (2.1, 3.8)]. Relationships between processing level and BMI-z score were not significant. Among this sample of low-income children, greater intake of highly processed foods was associated with lower dietary quality, but not weight status. Future research should explore prospective associations between food consumption by processing category and weight status in children.